Off-balance sheet items and the financial crisis: An empirical evidence of the United Kingdom Banks - Hemnani, Yash Harish (2015)
The last couple of decades, our financial systems around the world have drastically evolved and given rise to potentially extremely high levels of risk. Borrowing has become extremely easy and at cheaper rates than ever before, opening up a great source of investments to everyone for their specific risk and return needs. Have these complex financial products but in fact hampered our growth? What are the central banks doing about the same? How did we lead ourselves into the crisis and what have we done to avert any further ones? What were the main causes of this devastating fallout and how badly were we affected? By evaluating the role of off-balance sheet items in the process of securitization with context to the financial crisis of 2007-2008, it is possible to explain its root causes. These issues are addressed in this piece of work.